HCL technologies : leveraging technology for talent acquisition transformation - Patra, Yogita; Saxena, Richa; Sharma, Sunil (London : Indian Institute of Management, Ahmedabad, 2024)
HCL Technologies was known for its strategic innovation in the HR function. They had introduced iTAP in 2013 to fast track the recruitment process, which successfully contributed to the improvement of hiring process. However, by 2017, it was time for the HR function to realign itself to changing business needs. The goal was to make the entire process more transparent with the help of technology. They decided to implement advanced technology to create more intelligent recruitment system called Techruit. However, there was still a long way to go to align the talent acquisition process to business goals. As multiple competitors were competing to hire the same candidate in the IT industry, it was imperative to provide an experience that would help differentiate HCL as a preferred employer in prospective candidates’ minds. The user experience needed to be extended to the other two stakeholders as well, i.e. the recruiter and hiring manager. The top management believed that ‘what gets measured, gets managed.’ The clear directive was to improve and measure recruiter performance. While they wanted the recruitment process to retain swiftness, clear guidelines had to be adhered to maintain ‘Quality of Hire.’ The decision to invest in the technology would depend on the cost optimization and savings through process improvement. A core team called Talent Acquisition Centre of Excellence (TA CoE) was formed by the CHRO with clear directions to make the new process swift and choose the right metrics for recruiter performance measurement. The CoE team had to decide how to use technology for excellent user experience and select a combination of metrics to measure recruiter productivity without compromising on quality of candidates.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Strategic planning -- Case studies; Technological innovations -- Case studies